2020
DOI: 10.1111/are.14848
|View full text |Cite
|
Sign up to set email alerts
|

Emerging pathogens caused disease and mortality in freshwater mussels,Hyriopsis cumingii,in China

Abstract: In August 2019, massive mortalities of cultured Hyriopsis cumingii occurred in a local shellfish breeding experimental base in Chongqing, China. In this report, we identified 14 isolates from cultured mussels in mortality events and demonstrated that these strains caused mortality from 9% to 97%. Significant mussel mortality (p < .05) was observed in association with most isolates after bacterial challenge; however, considerable variation in the virulence of different isolates was noted, with survival ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Ammonia exposure also caused large interlamellar space, the exfoliation of cilia, and pyknosis of nucleus in the gills of H. cumingii. These have been observed in H. cumingii after bacterial challenge [57] and exposed to Microcystis aeruginosa under hypoxia [58]. The observed histological changes in our test indicated that ammonia caused severe damage to the internal physiology of the hepatopancreas and gills.…”
Section: Discussionsupporting
confidence: 68%
“…Ammonia exposure also caused large interlamellar space, the exfoliation of cilia, and pyknosis of nucleus in the gills of H. cumingii. These have been observed in H. cumingii after bacterial challenge [57] and exposed to Microcystis aeruginosa under hypoxia [58]. The observed histological changes in our test indicated that ammonia caused severe damage to the internal physiology of the hepatopancreas and gills.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, K. oxytoca can acquire antimicrobial resistance and carry multiple virulence genes, such as capsular polysaccharides and fimbriae [48]. The virulence of other species analyzed in this study, such as H. alvei [49], M. morganii [50], P. vulgaris [51], S. maltophilia [52], and R. planticola [53], has been previously reported.…”
Section: Virulence Factorsmentioning
confidence: 70%
“…Virulence Factor of Pathogenic Bacteria Database (VFDB) (http://www.mgc.ac.cn/ VFs/, accessed on 13 December 2022) was used to characterize virulence factors. Additionally, we prolonged the analysis to include virulence factors that are contained in several scientific publications [47][48][49][50][51][52][53].…”
Section: Virulence Factorsmentioning
confidence: 99%
“…213 Stenotrophomonas maltophilia and A. veronii were isolated from cultured H. cumingii from a large mortality event, and subsequent experimental infections resulted in myofiber degeneration and gill necrosis in infected mussels; intralesional bacteria were not reported. 214 Another study to investigate the immune response to bacterial infection at the transcriptomic level showed 5957 differentially expressed genes in H. cumingii challenged with A. veronii. 213 The study of bacteria in freshwater mussels is complicated by the fact that freshwater mussels constantly interact with bacteria in the aquatic ecosystem, use bacteria as a food source, 198 and host diverse bacterial taxa in health.…”
Section: Bacteriamentioning
confidence: 99%
“…213 Stenotrophomonas maltophilia and A. veronii were isolated from cultured H. cumingii from a large mortality event, and subsequent experimental infections resulted in myofiber degeneration and gill necrosis in infected mussels; intralesional bacteria were not reported. 214 Another study to investigate the immune response to bacterial infection at the transcriptomic level showed 5957 differentially expressed genes in H. cumingii challenged with A. veronii . 213…”
Section: Bacteriamentioning
confidence: 99%